Advances in the discovery of cathepsin K inhibitors on bone resorption. (1st January 2018) - Lu, Jun; Wang, Maolin; Wang, Ziyue; Fu, Zhongqi; Lu, Aiping; Zhang, Ge
Abstract: Cathepsin K (Cat K), highly expressed in osteoclasts, is a cysteine protease member of the cathepsin lysosomal protease family and has been of increasing interest as a target of medicinal chemistry efforts for its role in bone matrix degradation. Inhibition of the Cat K enzyme reduces bone resorption and thus, has rendered the enzyme as an attractive target for anti-resorptive osteoporosis therapy. Over the past decades, considerable efforts have been made to design and develop highly potent, excellently selective and orally applicable Cat K inhibitors. These inhibitors are derived from synthetic compounds or natural products, some of which have passed preclinical studies and are presently in clinical trials at different stages of advancement. In this review, we briefly summarised the historic development of Cat K inhibitors and discussed the relationship between structures of inhibitors and active sites in Cat K for the purpose of guiding future development of inhibitors.